(untitled) (Journal of Bio-Science, 2011)
Context: Development of resistance in human pathogens against conventional antibiotic necessitates searching indigenous medicinal plants having antibacterial property. Seven medicinal plants used actively in folklore, ayurvedic and traditional system of medicine were selected for the evaluation of their antimicrobial activity for this study. Objectives: Evaluation of the effectiveness of some medicinal plant extracts against four Gram-positive and five Gram-negative bacteria. Materials and Methods: The antibacterial activity of the crude ethanolic extracts obtained from the leaves of seven medicinal plants; viz., Andrographis paniculata, Catharanthus roseus, Adhatoda vasica, Vitex vegundo, Aloe vera, Flacortia ramontchi and Nyctanthes arbortristis were tested against nine bacteria at concentrations of 300-, 400- and 500 μg/ml. Standard antibiotic disc kanamycin (30μg/ml) was used for comparison. The minimum inhibitory concentration (MIC) of ethanolic extracts of the leaves of these medicinal plants were determined by testing the extracts on four Gram-positive and five Gram-negative bacteria by serial tube dilution method. Results: All the extracts have notable antimicrobial activities against the test organisms. The ethanolic extracts of the leaves showed the highest antimicrobial activities against Bacillus megaterium and Shigella dysenteriae for An. paniculata, Ad. vasica and Al. vera; Bacillus subtilis and Salmonella typhi for C. roseus and N. arbortristis; Staphylociccus aureus and Salmonella typhi for V. vegundo; and Bacillus subtilis and Shigella sonnei for F. ramontchi respectively. The extract of the plants had MIC values ranging from 32 to 128 mg/ml. All plant extracts showed no MIC against Shigella shiga and against Sarcina lutea only C. roseus showed MIC 128 mg/ml. Conclusion: The results revealed that the ethanolic extracts of the plants under present investigation have notable antimicrobial activities. Keywords: medicinal plants; antimicrobial screening; MIC; bacteria. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8788 JBS 2010; 18(0): 128-133